Respuesta :
Answer:
-12 or 5
Step-by-step explanation:
p² + (p+7)² = 169
p² + (p²+14p+49) = 169
2p² + 14p + 49 - 169 = 0
2p² + 14p - 120 = 0
2p² + 24p - 10p - 120 = 0
2p(p+12) - 10(p+12) = 0
(p+12)(2p-10) = 0
p+12 = 0 , or 2p-10 = 0
p = -12 or 5
Answer:
p = 3
Step-by-step explanation:
p² + (p +7)²=169
Open the bracket and solve the value in the bracket according to BODMAS
p^2 + p^2 + 7^2 = 13^2
Square Root the both side of the equation.
√{p^2} + √{p^2} + √{7^2} = √{13^2}
p + p +7 = 13
2p + 7 = 13
collect like term of the numbers
2p = 13 - 7
2p = 6
Divide both side by the coefficient of p.
2p/2 = 6/2
p = 3.